Expanding the boundaries of buyer-supplier agency problems: Moving from dyad to triad. Issue 3 (June 2022) - Yang, Yang S.; Choi, Thomas Y.; Carter, Craig R.; Yin, Rui
Abstract: Extant agency theory addresses dyads consisting of a principal and an agent. It informs us about how to overcome agency problems in the buyer-supplier relationship. In this conceptual paper, we propose a theoretical argument that if we expand the boundary conditions from dyads to triads, we find new solutions to dealing with agency problems. To the buyer-supplier dyad, we add the supplier's supplier, the buyer's other supplier, the supplier's other customer, and the buyer's customer. As such, we consider four types of triads in supply chains and propose that the buyer as the principal could reframe agency problems with the focal supplier by moving to one of these triads. In particular, we investigate alternative mechanisms that may reduce the level of goal incongruence, information asymmetry, and power asymmetry in the buyer-supplier relationship. Our conceptualization suggests that supply managers should look outside the buyer-supplier dyad for additional opportunities to resolve agency problems. Highlight: Known solutions for B–S agency problems are confined in the dyads; We combined agency theory and supply chain triad research; We identified new solutions as we expand the boundary from dyads to triads; These new solutions reduce goal conflict, information asymmetry and goal asymmetry; Supply managers should look outside the B–S dyad to resolve agency problems.